A STUDY OF RENAL FUNCTION IN ROENTGEN RAY INTOXICATION : RESISTANCE OF RENAL EPITHELIUM TO DIRECT RADIATION. - McQuarrie, Irvine (The Rockefeller University Press, 1922)
Our experiments give no support to the current belief that an x-ray nephritis may be produced by direct or indirect action of the hard Roentgen rays. Moderate doses of x-rays given repeatedly over considerable periods of time have no demonstrable influence on renal function or renal structure. With x-ray exposures of the abdomen and shielding of the kidneys fatal intoxication may be produced without the slightest disturbance of kidney function as measured by the ability of the kidney to eliminate phenolphthalein and urea. Large doses of the x-rays given directly over the kidney may cause a slight but distinct lowering of renal function which lasts for a period of a few days. We have been unable to recognize any corresponding histological change. We feel that the usual therapeutic doses of the x-rays can be given over the kidneys without apprehension. The renal tissue is much more resistant to x-rays than is the epithelium of the small intestine.